Derfor er historien autoritet - Alfred Bindslevs fortælling om dansk konservatisme - Skov, Christian Houlberg (Slagmark - Tidsskrift for idéhistorie, 2018)
Alfred Bindslev´s Konservatismens Historie i Danmark stands as an example of how history is used by groups and agents to form and maintain a historical and ideological identity. Bindslev claimed continuity and organic growth as the governing principle of history and reality as such. In claiming the authority of history he tried to preserve the old anti-liberal current in the modern conservative people’s party in the interwar years. This was done by using the authority of history to construct and maintain a dichotomy between a cluster of concepts related to the nation, conservatism and organic growth on one side and concepts related to liberalism, atheism and discontinuity on the other side.